Economic systems of foraging, agricultural, and industrial societies - Pryor, Frederic L. (Cambridge University Press, 2005)
Drawing upon the disciplines of economics, anthropology, statistics, and history, and employing a new and unified analytic approach, Frederic L. Pryor reformulates in this book the entire field of comparative economic systems. He examines large samples of foraging (hunting, gathering and fishing), agricultural, and industrial economies to explore four key questions: What are the distinct economic systems found in each group? Why do certain societies or nations have one economic system rather than another? What impact do economic systems have on the performance of the economy? How do these economic systems develop and change? The results provide a context that allows us to move beyond the chaos of case studies and ideological assertions to gain an overview of the development of economic systems over the millennia. It also raises a series of new analytic and empirical issues that have not hitherto been systematically explored.